The efficiency of using some integrated control methods in controlling the mealybug Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) - Ahmed Hassan Khudair Abbas; Ali Abdulhusien Kareem (Journal of Kerbala for Agricultural Sciences, 2024)
This study evaluated the efficiency of some integrated pest control methods to control the mealybug Phenacoccus solenopsis Tinsley under laboratory conditions. It was done by testing the efficiency of some methods, such as insecticides Conan and Actrara, entomopathogenic fungi Beauveria bassiana, Nano Calcium silicate, and mineral oil. This experiment was carried out in the insect laboratory for postgraduate studies at the College of Agriculture, University of Kerbala. The results prove that insecticides Conan and Actara significantly affect both nymphs and adults, where the average percentage of nymphs mortality within 24 hours of treatment was 100%. The concentrations of the Conan pesticide were (300 - 400 - 500 mg/L) Whereas the Actara pesticide was in concentrations (0.20 – 0.25 – 0.30 ml/L) respectively. Likewise, the rate of mortality of adults within 24 hours of treatment with Actara and its three concentrations used (0.20 - 0.25 - 0.30 ml/L) and Conan with three concentrations as well (300 - 400 - 500 mg/L) reached 100%. Based on the study's results, both insecticides, Conan and Actara, can be used due to their superiority in mortality rates. In contrast, the mortality rate was 100% in both nymphs and adults within 24 hours of treatment compared to the other treatments used.